2017
DOI: 10.1038/pr.2017.83
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Sex and age differences in phenylephrine mechanisms and outcomes after piglet brain injury

Abstract: Background Traumatic brain injury (TBI) is the leading cause of injury related death in children, with boys and children under 4 having particularly poor outcomes. Cerebral autoregulation is often impaired after TBI, contributing to poor outcome. In prior studies of newborn pigs, phenylephrine (Phe) preferentially protected cerebral autoregulation in females but not males after TBI. We hypothesized that, in contrast to the newborn, Phe prevents impairment of autoregulation and tissue injury following TBI in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Our other recent studies using different vasoactive agents have observed the opposite, building the argument for use of a precision medicine approach in treatment of pediatric TBI. For example, Phe and NE have been shown to worsen cerebral autoregulation and histopathology in male, but not female newborn piglets and male and female juvenile pigs after FPI (Armstead et al 2010 a,b, 2016 a,b; Curvello et al 2017). In contrast, EPI prevents impairment of cerebral autoregulation and histopathology in newborn male and female and juvenile female but not juvenile male pigs after FPI (Armstead et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our other recent studies using different vasoactive agents have observed the opposite, building the argument for use of a precision medicine approach in treatment of pediatric TBI. For example, Phe and NE have been shown to worsen cerebral autoregulation and histopathology in male, but not female newborn piglets and male and female juvenile pigs after FPI (Armstead et al 2010 a,b, 2016 a,b; Curvello et al 2017). In contrast, EPI prevents impairment of cerebral autoregulation and histopathology in newborn male and female and juvenile female but not juvenile male pigs after FPI (Armstead et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Phe and NE has been shown to protect cerebral autoregulation and limit histopathology in newborn females, and juvenile male and female but not male newborn pigs after fluid percussion brain injury (FPI) (Armstead et al 2010b, 2016 a,b; Curvello et al 2017). In contrast, EPI prevents impairment of cerebral autoregulation and limits histopathology in newborn male and female and juvenile female but not juvenile male pigs after FPI (Armstead et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the most common form of TBI in infants < 1 year of age is abusive head trauma (AHT), also known as the shaken baby syndrome [19]. In addition, a substantial body of work (discussed later in this review) has also focused on cerebrovascular derangements in juvenile piglets (3–4 weeks of age) in order to model findings to the neurocritical care of children with severe TBI [2023]. A large animal model of developmental brain injury was also designed to study AHT using 7–10 day old lambs [2427].…”
Section: Unique Facets Of the Developing Brain—relevance To Pediatricmentioning
confidence: 99%
“…Following that work, the Armstead laboratory has used this model to study a large number of secondary injury mechanisms, with a general focus on studies germane to the cerebral circulation and its regulation. A complete review of the many studies performed is beyond the scope of this review, however, key issues such as the mechanisms of autoregulation and its impairment after injury [21], sex differences in both the injury and vascular responses as well as consequences of therapy [22], and reports on pre-clinical approaches to optimizing perfusion and mitigate neuronal death after injury [23] highlight some of the areas of investigation. Insight into the roles of prostanoids, oxidative signaling, kinases, and endothelin in vascular dysregulation has been provided.…”
Section: Unique Facets Of the Developing Brain—relevance To Pediatricmentioning
confidence: 99%
See 1 more Smart Citation